It takes a church to raise a Christian how the community of God transforms lives - Bolsinger, Tod E. (Grand Rapids, MI Brazos, 2004)
Includes bibliographical references and index.
Revision of the author's doctoral thesis -Fuller Theological Seminary, 1991.
Keywords: Spiritual life -- Christianity